Lived Experiences of Faculty Members In Institutes of Higher Education Amidst Covid-19 - Mary Grace M. Villaflores (Formosa Journal of Multidisciplinary Research, 2023)
With the current onslaught of the COVID-19 pandemic, higher education institutions in most countries have shifted from the traditional to online mode of delivery. This study reports the findings of a survey examining the online teaching experiences of faculty members in HEIs and how the pandemic impacted the faculty work within the higher education setting. Participants consisted of selected faculty members from a local college in the City of San Jose Del Monte, Bulacan. Findings reveal that there were various techniques and preparations employed by the faculty members in order to conduct an effective and efficient remote and online learning experience for their students. Remote online learning also offers faculty members more options for engaging instructional activities. It allows them to be more resourceful considering that they cannot meet in person with their students as with the traditional teaching mode. Despite the constraints and restrictions in conducting classes online, such as poor internet service, restricted contact between teachers and students, to name a few, most of the respondents, nevertheless, assessed themselves to be still efficient and effective as teachers.